The Analysis of Quality of Health Services Effect against Patient Satisfaction Patients at Royal Prima Medan Hospital - Delpini Simanjorang; Riyani Susan Bt Hasan; Mangatas Silaen; Ermi Girsang (Universitas Muhammadiyah Yogyakarta, 2019)
Data on visits of general patients’ outpatient Royal Prima Medan Hospital from February to August 2018 showed a decline. One factor that causes a decrease in patient visits is patient dissatisfaction with the hospital. Indicators of patient satisfaction can consist of health insurance consisting of physical evidence, reliability, responsiveness, assurance and certainty, and empathy provided by the hospital to its customers. Quantitative research using cross-sectional and the number of respondents’ as many as 89 people using accidental sampling technique. Data analysis was done by multiple linear regressions. A significant influence between the qualities of health services is needed at 97.2% with a significance value of 0,000 for patient satisfaction. The results of this data analysis indicate that patients are satisfied with the health services provided by Royal Prima Medan Hospital. This shows that there are other factors that come out of this study that causes rejection of patient visits. Obtained a significant between the qualities of health services by 97.2% of patient satisfaction. For this reason, Royal Prima Medan Hospital is expected to be able to maintain and improve the quality of health services that already exist in hospitals, and find and improve other factors that cause a decrease in patient visits at the hospital.